The degradation of gas turbine blade materials and additively manufactured Alloy 625 in high temperature CO2 environments - Norman, Boma Phoebe (Cranfield University, 2025)
The need for a cleaner and more efficient method of electricity production has gained significant attention. The Allam cycle is a highly recuperated Brayton cycle that utilises supercritical (sCO2) under conditions exceeding 760°C and 30 MPa, and presence of contaminants such as SO2, H2O, and N2. The selection and durability of materials remain a critical concern. The influence of these impurities in sCO2 environments, or how manufacturing techniques like traditional or additive manufacturing (AM), laser powder bed fusion (LPBF), affect oxidation behaviour, is not fully explored. This thesis examines the high-temperature oxidation behaviour of nickel-based superalloys under Allam cycle conditions at atmospheric pressure, focusing on the effects of impurities, manufacturing techniques (LPBF), and surface conditions. Isothermal oxidation tests were conducted at 800°C in controlled gas environments. These included CO2 + 2.7 mol% H2O + 1.43 mol% N2 + 0.17 mol% O2 + 300 ppm SO2 and CO2 + 2.7 mol% H2O + 0.17 mol% O2. Contaminants degrade protective oxide scales, leading to internal oxidation and nitridation. Chromia-forming alloys, Rene 80 and IN738, exhibited accelerated mass gain and oxide breakdown, whereas alumina-forming alloys, CM247 and Marm247, demonstrated enhanced oxidation resistance. Thermal barrier coatings (TBCs), comprising YSZ and a bond coat system on CM247, provided further protection by limiting the ingress of reactive species and promoting the formation of stable thermally grown oxides. Surface condition affects oxidation in LPBF Alloy 625. Polished, solution-treated samples had better chromia scales and lower oxidation rates than as-built or rough surfaces. Both polished and as-built samples, including wrought, formed chromia and Nb- and Mo-rich phases. Solution-treated LPBF showed improved resistance due to microstructure, leading to stable oxide layers and fewer ridge like features compared to as-built. Although wrought alloy developed a thicker oxide, LPBF's slower-growing oxide indicates potential for long-term durability.
Keywords: Oxidation; Additive manufacturing; impurities; surface roughness; nickel-based superalloys